Mental and Physical Health Correlates of Financial Difficulties Among African-American Older Adults in Low-Income Areas of Los Angeles - Evans, Meghan C.; Bazargan, Mohsen; Cobb, Sharon; Assari, Shervin (Frontiers in Public Health, 2020)
Background: While financial difficulties correlate with mental and physical health status, less is known about these associations among economically disadvantaged African-American (AA) older adults. Objective: This study explored mental and physical health correlates of financial difficulties among AA older adults in low-income areas of south Los Angeles. Methods: A cross-sectional study on 740 AA older adults (age ≥ 55 years) conducted in South Los Angeles between 2015 and 2018. Independent variable was financial difficulties. Outcomes were depressive symptoms, chronic pain, chronic medical conditions, self-reported health, and sick days. Age, gender, educational attainment, living alone, marital status, smoking, and drinking were also measured. Zero order (unadjusted) and partial (adjusted) correlates of financial difficulties were calculated for data analysis. Adjusted (partial) bivariate correlations controlled for age, gender, education, marital status, living alone, and health insurance. Results: In adjusted analyses, financial difficulties were positively associated with chronic pain, chronic medical conditions, self-rated health, sick days, and depressive symptoms. Conclusion: Financial difficulties seem to be linked to chronic pain, chronic medical conditions, self-rated health, sick days, and depressive symptoms. The results advocate for evaluation of social determinants of health in providing health care of AA older adults. Addressing financial difficulties may help with the health promotion of low-income AA older adults in urban areas.